Economic Exploitation of Children: An Integrated Handling Model for the Protection of Children's Constitutional Rights (Study in Pati Regency) - Lutfiana, Sofia Ayut; Sri Utari, Indah (Law Research Review Quarterly, 2025)
Economic exploitation of children is still a serious problem that occurs in various regions, including in Pati Regency, and has a direct impact on the violation of children's rights. This problem is generally triggered by the socio-economic conditions of vulnerable families and low legal awareness of the community, so that children are often used as a means to gain economic benefits. This study aims to analyze law enforcement against the crime of economic exploitation of children in Pati Regency and formulate an integrated handling model in the context of protecting children's constitutional rights. The research method used is sociological juridical with a qualitative approach, through the collection of primary data obtained from the public and law enforcement officials, as well as secondary data sourced from laws and regulations and literature studies. The results of the study show that normatively the legal apparatus for child protection has been adequate, but its implementation at the regional level has not been running optimally. Law enforcement is still dominated by preventive efforts, while repressive actions against exploiters have not been carried out firmly and consistently. The low legal culture of the community is also a factor that inhibits the effectiveness of child protection. This study concludes that it is necessary to strengthen fair law enforcement, increase cross-sector coordination, and build community legal awareness as part of an integrated handling model to suppress the practice of economic exploitation of children and ensure the protection of children's constitutional rights in a sustainable manner.